(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In the process of communication, the speaker is not limited to conveying simple information about the events in reality, but also expresses his attitude towards this event and tries to influence the mind and emotions of the listener. Interrogative sentences are the linguistic manifestation of a speech act with the purpose of asking a question. In other words, a question sentence is a syntactic device that corresponds to a certain type of speech act. Therefore, while describing the question sentence as a surface structure with certain syntactic features, it should also be noted that it has semantic properties.